Analisis SWOT terhadap usaha mebel Karya Wijaya di Sleman, Daerah Istimewa Yogyakarta - Ali Jufri; Bhenu Artha (Universitas Widya Mataram, 2022)
The purpose of this study was to determine the strategy that must be applied by the Karya Wijaya furniture business in Sleman, Special Region of Yogyakarta. This strategy must be applied to stay afloat in the face of business competition. The SWOT analysis has identified the strengths, weaknesses, opportunities, and threats of Karya Wijaya's furniture business in Sleman, Special Region of Yogyakarta. Its strengths lie in production, marketing, management and personnel. The weaknesses lie in inadequate equipment and there is no specific standard for the payment system. Opportunities that are owned, namely the market share for furniture is very open. The existing threat is the low capacity of the technology used, especially information technology. To be better known to the public, Karya Wijaya's furniture business must enter the marketplace and do online advertising and marketing.